STUDY OF THE NASAL SEPTUM AND ITS VARIATIONS THROUGH DYNAMIC NAVIGATION USING A NEW CONE-BEAM COMPUTED TOMOGRAPHY SOFTWARE IN A BRAZILIAN SUBPOPULATION (CIPEEX, 2025)
Objective: To determine the frequency of nasal septum deviation (NSD) and the anatomical variations of the nasal septum, in dynamic navigation using a new cone-beam computed tomography software in a Brazilian subpopulation. Material and method: The study sample consisted of 200 cone-beam computed tomography exams from patients of both sexes. The inclusion criteria involved exams that presented the nasal septum within the field of view. For the determination of nasal septum deviation, in cone-beam computed tomography images, the following were related: gender, age, nasal septum deviation (presence or absence). The method for determining the anatomical variations of the nasal septum, in cone-beam computed tomography images, included the Mladina classification. Statistical analysis was performed using the Statistical Package for the Social Sciences software, version 20 (SPSS, Chicago, IL), with variables described as frequencies and percentages and evaluated by the chi-square test. There was a prevalence of female individuals and in the age group between 31 and 50 years. 51.00% of the sample presented a normal nasal septum. Among the population that presented septum deviation, it was observed that 15.50% presented Type III deviation, while 13.50% presented Type I deviation, 8.50% presented Type II deviation, 4.50% presented Type IV deviation, 4.0% Type V deviation, 3.50% Type VI deviation, and 0.50% Type VII deviation.
Keywords: Anatomy; nasal septum; maxillary sinus; cone-beam computed tomography